PEMBELAJARAN PRAKARYA MATERI KERAMIK DENGAN MENGGUNAKAN MEDIA BAHAN LUNAK FLOUR CLAY DI KELAS VIII A SMP NEGERI 1 PADANG PANJANG - M. Fadhil; Saputra, Andra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the learning process of Craft in ceramic materials using flour clay as a soft-material learning medium in Class VIII A of SMP Negeri 1 Padang Panjang. The findings indicate that the learning process using flour clay was carried out through three stages: planning, implementation, and evaluation. During the implementation stage, students created design sketches, prepared flour clay dough, shaped ceramic craft products, completed the finishing process, and presented their work. The use of flour clay as a learning medium enhanced students' creativity, motor skills, critical thinking, communication, and collaboration throughout the learning process. In addition, flour clay is easy to obtain, safe to use, and cost-effective, making it an effective learning medium that provides a more active and enjoyable learning experience while supporting the achievement of learning objectives in soft-material craft learning within the Craft subject.